O impacto do desenvolvimento da tecnologia no século XXI sobre o seguro contra incêndio - Cavalcante, Rodolfo Henrique de Paiva (2021)
This dissertation addressed the topic of Technological Innovation in Fire Insurance, with the objective of analyzing and evaluating the advantages, disadvantages and challenges of new technologies, which emerged in the Fourth Industrial Revolution. The methodology adopted was based on applied, exploratory research, in a qualitative and quantitative approach, associating referential bibliographic research with factual and true information about the importance of Technology and Fire Insurance. First, a historical search for World Insurance was made, focusing on Fire Insurance. After all the analysis and studies, it is perceived as an advantage that new technologies have brought to the area of fire insurance, greater ease in the identification and monitoring of fires in buildings and forests, implementing tools that can be developed with the future of technology and go beyond fire identification. As a disadvantage, there is that, due to the implementation of new technologies, one must take into account, although minimal, the risk of failures in infrastructure, which may lead to a more vulnerable risk due to the little experience that companies still have; in addition, another risk that can happen is also the cyber risk, where one of the fire identification machines may have a failure and cause a cyberattack, thus affecting the analysis of fires. The ethical impact can also occur, since several sectors have been affected by the substitution of labor, causing profound changes in the labor market and high risk to jobs in several areas. The challenges imposed by the new technologies for the fire insurance area point to a greater demand in the production of flying machines and cameras to report fires, with guarantee that there is no failure, that is, the improvement of technology in fires and the greater attention that companies should pay to Fire Insurance. Finally, a study was carried out on the SUSEP SES platform covering the period from 2001 to 2019, aiming to identify the factors that may have impacted on the perceived changes, such as the creation of Insurtechs and the internationalization of companies, in addition to the mergers that occurred in some companies